Research of Rectification Technology of Electric Locomotive under Unbalanced Three-phase Voltage - LV Kang-fei; SHI Chao-yue (Gong-kuang zidonghua, 2012)
In view of problem of negative sequence current component in AC side of traditional PWM rectifier because of unbalanced three-phase voltage existed in converter system of underground DC electric locomotive, the paper proposed a control strategy of restraining negative sequence current component of AC side of PWM rectifier under unbalanced three-phase voltage. It introduced implementation of the control strategy in details. The results of simulation and field experiment showed that current wave of AC side of PWM rectifier is close to sine wave and realizes running with unity power factor after using the control strategy.